The association between 11C-methionine uptake, IDH gene mutation, and MGMT promoter methylation in patients with grade II and III gliomas. Issue 8 (August 2020) - Okita, Y.; Shofuda, T.; Kanematsu, D.; Yoshioka, E.; Kodama, Y.; Mano, M.; Kinoshita, M.; Nonaka, M.; Fujinaka, T.; Kanemura, Y.
Abstract : Aim: To evaluate the association between 11 C-methionine positron-emission tomography ( 11 C-methionine PET) findings, isocitrate dehydrogenase ( IDH ) gene mutation, and O 6 -methylguanine-DNA methyltransferase ( MGMT ) promoter methylation in patients with grade II and III gliomas. Materials and methods: Data were collected from 40 patients with grade II and III gliomas who underwent both magnetic resonance imaging (MRI) and 11 C-methionine PET as part of their pre-surgical examination. IDH mutation was examined via DNA sequencing, and MGMT promoter methylation via quantitative methylation-specific polymerase chain reaction (PCR). Results: A threshold of MGMT promoter methylation of 1% was significantly associated with tumour/normal tissue (T/N) ratio. The T/N ratio in samples with MGMT promoter methylation ≥1% was higher than that in samples with MGMT promoter methylation <1%, and the difference was statistically significant ( p =0.011). Reliable prediction of MGMT promoter methylation (<1% versus ≥1%) was possible using the T/N ratio under the receiver operator characteristic (ROC) curve with a sensitivity and specificity of 75% each (cut-off value=1.6: p =0.0226, area under the ROC curve [AUC]=0.76172). Conversely, the T/N ratio had no association with IDH mutation ( p =0.6). The ROC curve revealed no reliable prediction of IDH mutation using the T/N ratio ( p =0.606, AUC=0.60577). Conclusion: 11 C-methionine PET parameters can predict MGMT promoter methylation but not IDH mutation status. 11 C-methionine uptake may have limited potential to reflect DNA methylation processes in grade II and III gliomas. Highlights: 11 C-methionine PET has the potential to predict MGMT promoter methylation status. 11 C-methionine PET was not a reliable marker for IDH mutation status. 11 C-methionine PET may have limited potential to reflect DNA methylation processes.